Prediction of Heart Disease Using Machine Learning Algorithms - Rajesh, N; T, Maneesha; Hafeez, Shaik; Krishna, Hari (International Journal of Engineering and Technology, 2018)
Heart disease is the one of the most common disease. This disease is quite common now a days we used different attributes which can relate to this heart diseases well to find the better method to predict and we also used algorithms for prediction. Naive Bayes, algorithm is analyzed on dataset based on risk factors. We also used decision trees and combination of algorithms for the prediction of heart disease based on the above attributes. The results shown that when the dataset is small naive Bayes algorithm gives the accurate results and when the dataset is large decision trees gives the accurate results.Â Â